Optimal treatment targets for lupus nephritis using per-protocol repeat kidney biopsy findings at 2 years and clinical data up to 5 years: a single-center observational study - Hidetoshi Kagawa; Ryutaro Yamanaka; Ai Matsubara; Tatsuyuki Inoue; Reika Hayashi; Natsuki Kubota; Tsutomu Hiromasa (SAGE Publishing, 2024)
Background: The criteria for remission in both clinical and pathological contexts for lupus nephritis (LN) remain controversial. Objectives: To identify optimal short-term goals (remission criteria) for LN predicting long-term success at 5 years, using repeat kidney biopsy (Biopsy 2) and clinical data. Design: Single-center observational study. Methods: Twenty-three consecutive LN patients undergoing Biopsy 2 2 years post-induction therapy were evaluated. Two ideal long-term goals at 5 years were defined as: "A," Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) = 0 and prednisolone (PSL) ⩽5 mg/day, and "B," proteinuria ⩽0.2 g/day with a normal serum creatinine level and PSL ⩽5 mg/day. Histologically, the electron-dense deposit (EDD) score grades immune deposits based on their intensity, amount, and location. A score of ⩽1 was defined as "electron microscopy remission (ER)." Results: Conventional renal indices failed to predict long-term goals. The short-term goals with an accuracy (area under the curve: 95% confidence interval) of ⩾0.8 predicted long-term goals: "A at 5 years" (A-5y), A-2y (0.91: 0.79-1.00), DORIS-R-2y (0.87: 0.72-1.00), EDD score (0.85: 0.70-1.00), B-2y (0.83: 0.66-0.99), and SLEDAI-R-2y (0.82: 0.66-0.98) as well as "B at 5 years" (B-5y), A-2y (0.87: 0.73-1.00), B-2y (0.87: 0.73-1.00), EDD score (0.85: 0.69-1.00), and DORIS-R-2y (0.83: 0.67-0.99). EDD scores predicted A-5y, B-5y, and PSL dose at 5 years in proportion to the score. The clinical and histological goals aligned. Conclusion: The best predictive short-term goal was A-2y. Concordance between clinical remission (A-2y, B-2y, and DORIS-R-2y) and histological remission (ER) at 2 years suggests optimal short-term goals for LN.